A qualitative study of women's perceptions of emergency alert mobile application usability / Mohd Fared Md Said - Md Said, Mohd Fared (2017)
This study attempts to identify human emotion and effectiveness of this application at the time of burglary based on the perception of the women. The background of smartphone, application and a burglary has been explained. The latest technology has enabled smartphone more useful for the purposes of health and safety. Four usability characteristics have been identified that became the pre-defined themes. Interviews were conducted to obtain information needed for the study. There were six participants who have been interviewed and shared their experiences and feedbacks. The interviews data has been transformed into transcript for analysis. The methodology adopted is an interpretative phenomenological analysis that refers to the construction of theme based on the category that has been identified on the transcript. Results of human emotions have been identified, namely, panic, anxious and fear. Most of the participants agreed that the activation of panic button must be effortless. The user interface should be simple and meaningful. Further, the findings showed how this application is less effective during the burglary according to the perception of women. It was found that human emotion has some influential values to the usability and effectiveness of this application. Based on the participants' feedbacks, some suggestions for improvement were highlighted through a usable model and implementation for further research.